In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan. Issue 23 (2nd December 2021) - Rauf, Abdur; Bawazeer, Saud; Naseer, Muhammad; Alhumaydhi, Fahad A.; Aljohani, Abdullah S. M.; Habib, Aamir; Khan, Raheem; Jehan, Urooj; Qureshi, Muhammad Nasimullah; Khan, Majid; Farooq, Umar; Kassenov, Amirzhan; et al.
Abstract: The current study aims at exploring enzyme inhibition of four species of medicinal herbs, namely Senna bicapsularis, Thevetia peruviana, Nerium oleander and Vinca major . Plant selection was done on the basis of their therapeutic uses by local practitioners. The crude methanolic extracts of these plants were tested for their α -glycosidase and urease enzyme inhibition potential. The observed urease inhibitory potential for the crude extract of S. bicapsularis, T. peruviana and N. oleander were 8.3 ± 0.33 μg, 6.98 ± 0.98 μg and 9.56 ± 1.43 μg, respectively while the V. major did not show any inhibition. In addition, the IC50 value for Thiourea was 22.3 ± 1.14 μg. The crude extracts of S. bicapsularis, T. peruviana, N. oleander, V. major were shown to inhibit α -glycosidase activity with an IC50 value of 630.3 ± 0.03 μg, 700.7 ± 2.43 μg, 430.4 ± 3.97 μg, and the standard (acarbose) 880 ± 1.03 μ M, respectively. Based on the TLC profile, the extract of S. bicapsularis was subjected to column chromatography and the major component named rhein (1 ) was identified. Compound 1 exhibited excellent urease and α -glycosidase inhibitory activity with an IC50 value of 7.4 ± 0.32 and 622.3 ± 1.03 μ M, respectively. Graphical Abstract: